Same but different: A systematic reassessment of the Hebius khasiensis Boulenger, 1890 (Reptilia: Squamata: Natricidae) species complex from the Indo-Burma biodiversity hotspot supports the revalidation of Natrix gilhodesi Wall, 1925 as a valid species - Bohra, Sanath Chandra; Nguyen, Tan Van; Vogel, Gernot; Lalremsanga, Hmar Tlawmte; Biakzuala, Lal; Das, Madhurima; Warjri, Holiness; Thongni, Goldenstar; Poyarkov, Nikolay A.; Purkayastha, Jayaditya (Zootaxa, 2025)
This study provides new insights into the systematics of the natricid species Hebius khasiensis Boulenger sensu lato. Our findings are based on recent collections from northeast India, including the type locality in the Khasi Hills, Meghalaya, and the examination of its syntypes. There is a species named Natrix gilhodesi Wall from Kachin State, Myanmar, which is currently considered a subjective junior synonym of H. khasiensis, but molecular data based on the mitochondrial gene analysis show that populations from northeast India and Kachin, Myanmar are deeply divergent from each other. Here, we redescribe H. khasiensis and designate an adult female from its syntypes as the lectotype for the taxonomic stability of the given species. We also revalidate Natrix gilhodesi from Myanmar as a valid species of the genus Hebius based on molecular and morphological parameters.